Crystallization and X-ray diffraction analysis of the HMG domain of the chondrogenesis master regulator Sox9 in complex with a ChIP-Seq-identified DNA element - Vivekanandan, Saravanan (2016)
Sox9 is a fundamental sex-determining gene and the master regulator of chondrogenesis, and is involved in the development of various vital organs such as testes, kidney, heart and brain, and in skeletal development. Similar to other known Sox transcription factors, Sox9 recognizes and binds DNA with the consensus sequence C(T/A)TTG(T/A)(T/A) through the highly conserved HMG domain. Nonetheless, the molecular basis of the functional specificity of Sox9 in key developmental processes is still unclear. As an initial step towards a mechanistic understanding of Sox9 transcriptional regulation, the current work describes the details of the purification of the mouse Sox9 HMG domain (mSox9HMG), its crystallization in complex with a ChIP-Seq-identified FOXP2 promoter DNA element and the X-ray diffraction data analysis of this complex. The mSox9HMG-FOXP2 promoter DNA complex was crystallized by the hanging-drop vapour-diffusion method using 20% PEG 3350 in 200 mM sodium/potassium phosphate with 100 mM bis-tris propane at pH 8.5. The crystals diffracted to 2.7 Å resolution and the complex crystallized in the tetragonal space group P41212, with unit-cell parameters a = b = 99.49, c = 45.89 Å. Crystal-packing parameters revealed that asymmetric unit contained one mSox9HMG-FOXP2 promoter DNA complex with an estimated solvent content of 64%.